What can intellectual property law learn from happiness research? - Estelle Derclaye (Edward Elgar Publishing, 2013)
As the description of the 2012 ATRIP congress's theme highlights, traditionally, scholars have used historical, doctrinal or comparative analyses, law and economics, political economy or philosophy, to discuss intellectual property law. Other methods such as empirical analysis, international relations, and human development are more recent. This chapter looks at intellectual property law in a new way, namely through the angle of happiness or well-being research. The field of happiness research is not that recent but strangely, so far, happiness researchers have hardly discussed the relationship between well-being and technology despite the pervasive role of the latter in contemporary society. Likewise, the discussion of happiness is also rare in the legal field (except of course in (mental) health law) and it is absent from intellectual property law, except indirectly through the discussion of the capability approach in the discourse on intellectual property and development. I consciously leave the capability approach for another article but it needs to be noted that there are parallels to be drawn between the application of happiness research on the one hand and the capability approach on the other hand, to intellectual property law. In effect, the two approaches converge or are complementary in many respects. There is a debate to be had about the value of happiness research for the field of intellectual property law.